Development and Preliminary Validation of a Simplified-Wording Form of the Multidimensional Personality Questionnaire. (August 2013) - Patrick, Christopher J.; Kramer, Mark D.; Tellegen, Auke; Verona, Edelyn; Kaemmer, Beverly A.
The Multidimensional Personality Questionnaire (MPQ) assesses a range of personality characteristics pertaining to affective and interpersonal style, behavioral restraint versus disinhibition, and capacity for sensory and imaginal engagement. Its 11 lower order trait scales map onto 3 higher order factors that reflect temperament dimensions. Its content and measurement properties have made the MPQ useful for elucidating constructs relevant to normal and abnormal behavior and investigating their neurobiological underpinnings. However, a barrier to its use in certain populations is the reading difficulty of some MPQ items. We describe efforts to develop a simplified-wording form, the MPQ-SF, composed of items readable at or below the seventh grade level (with most below sixth grade). Simplified-wording items demonstrated high convergence with original-wording items, and resulting trait scales showed adequate internal consistencies and appropriate higher order structure. The availability of a simplified version expands the potential utility of the MPQ to a wider range of samples.